Self-Compacting Concrete with Partially Substitution of Waste Marble: A Review - Jawad Ahmad; Zhiguang Zhou; Ahmed Farouk Deifalla (International Journal of Concrete Structures and Materials, 2023)
Abstract Self-compacting concrete (SCC) is also seen as unsustainable since it uses a lot of natural resources. Recent researchers have focused on lowering construction costs and partially replacing cement with industrial waste. It is possible to effectively use various industrial wastes in concrete as cement or aggregates. Among these wastes, waste marble (WM) is a useful choice, and researchers have been interested in using WM in concrete for a couple of years. However, to pinpoint the advantages and recent advancements of research on WM as an ingredient of SCC, a comprehensive study is necessary. Therefore, the purpose of this study is to do a compressive evaluation of WM as an SCC ingredient. The review includes a general introduction to SCC and WM, the filling and passing capability of SCC, strength properties of SCC, durability, and microstructure analysis of SCC. According to the findings, WM improved the concrete strength and durability of SCC by up to 20% substitution due to micro-filling and pozzolanic reaction. Finally, the review also identifies research gaps for future investigations.